FORMULASI DAN UJI MUTU FISIK SEDIAAN GEL EKSTRAK BUNGA TELANG (Clitoria ternatea L.) SEBAGAI ANTISEPTIK TANGAN - Moh Farhan (Fakultas Farmasi Institut Kesehatan DELI HUSADA Deli Tua, 2023)
Hands are one of the media for microbial growth, dirty hands become a breeding ground for microbes such as Staphylococcus aureus and Escherichia coli or other bacteria. How to maintain hand hygiene is to wash your hands with soap or use an antiseptic (hand sanitizer). Antiseptic preparations are substances that have been widely used to inhibit the growth and kill microorganisms that exist around the body surface, for example on the palms of the hands that often come into contact with the surface of an object. One of the natural ingredients that has the potential to be developed as a hand antiseptic is telang flower (Clitoria ternatea). This research will formulate antiseptic gel preparations from telang flower extract, and how to test the physical quality of antiseptic gel preparations from telang flower extract. The method used for the extraction process here uses the maceration method, to maintain the antimicrobial compounds contained in the telang flower, followed by testing the physical characteristics and quality of the telang flower gel preparation, including, Organoleptic Test, pH test, Viscosity test, Homogeneity test, Spreadability test, adhesion test. After testing the characteristics and physical quality of the gel preparations of telang flower extract, the results were quite optimal, namely with a pH value in the range of 4.26-4.41 according to skin pH, and for viscosity at a value of 64% - 33%, in accordance with the characteristics of a good gel. Telang flower extract can be made and formulated as an antiseptic hand gel preparation. Variations in the concentration of the extract used greatly affect the characteristics of the gel preparation, starting from pH, viscosity, adhesion, and dispersion. The higher the concentration of the extract used, the lower the viscosity value, and the lower the pH value. The pH value and viscosity value for all formulas were in accordance with the skin parameter criteria, namely 3.5-6.5. Based on research conducted, Formula 3 using a concentration of 0.5 has. the most optimal gel preparation